Building A Culture Of Shame In Malay Society Against Corruption Practices In North Sumatera - Nelvitia Purba; Mukidi Mukidi; Nila Afningsih (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
This study focuses on the application of building a Malay culture against corrupt practices. This research will reveal how the application builds the Malay culture so that it can fight against corrupt practices. The results of this study can be used as a reference in fighting corruption practices that have become a national problem and improving the quality of life of Indonesian, especially in North Sumatra. This type of research uses qualitative methods that are juridical normative empirical, namely library research by collecting a number of data. The result of the study show that there are many values in local wisdom, as in Tunjuk Ajar Melayu which has almost been forgotten by generations. Corruption is a behavior that is influenced by culture, so that corruption can be minimized with a cultural application approach to building a Malay culture. The Malay culture is a guideline in the form of Malay Teachings, which is packaged in Malay local wisdom, containing advice, teaching or advice from generation to generation. The increase in corrupt behavior occurs not because of a developing Malay culture, but because society has left this culture, thus providing support for corruption